Monascus sp. Pigment Potency as Simple Preservative in Food Ingredients - Wahyu Aji Mahardhika; Maulida Aqlinia; Delfiani Anggias Putri; Vincentia Fenice Angger Maherani; Sri Listiyowati; Firda Sri Efendi (Jurnal Biologi Tropis, 2022)
Everyday foodstuffs such as tofu, chicken, and fish are ingredients that have a short shelf life if stored outdoors or in the open air. The fungus Monascus sp. is a fungus whose pigment is often used in giving color to food. This study aims to determine the potential of Monascus sp pigment isolated from commercial red rice (Angkak) as a preservative in tofu, chicken, and fish at room temperature. The methods used included isolation of the fungus Monascus sp from commercial red rice (Angkak), macroscopic and microscopic morphological characterization, solid fermentation using rice, harvesting pigments with water solvent, and pigment resistance tests on tofu, chicken meat, and fish. The results obtained from the application of the crude extract of the Monascus sp. pigment in fish survived for two days, chicken meat lasted up to three days, and tofu lasted four days. Each experiment had different results during the organoleptic test and compared to a positive control, namely turmeric, proving that turmeric was still better at resisting food spoilage. This research needs to be investigated further regarding the potential if the pure extract of the Monascus sp pigment is used.